Mechanical properties and failure analysis of PLA/copper composites fabricated by fused deposition modelling - Kumar R.V.; Kumar K.R.; Soms N. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The Fused Deposition Modelling process is an additive manufacturing process that is influenced by numerous parameters that affect the strength of the components. This paper article is dedicated to the study of the effects of Fused Deposition Modelling parameters on the strength of PLA/Copper infill composites. The influence on tensile, impact and flexural strength was investigated by varying the process parameters. The printer properties, i.e. the Nozzle Temperature and Printing speed, and the processing parameters, i.e. the Layer Thickness and the density of the infill are the most important parameters considered in this study. Mathematical models were developed to predict the strength of the composites as the process parameters were varied. The strength of the composites decreased with increasing layer thickness and printing speed. On the other hand, in the strength of the composites increased when the nozzle temperature and the density of the infill were increased. The composite samples were subjected to failure analysis to determine the fracture mechanisms. Both brittle and ductile failure mechanisms were observed in the samples, which are influenced by the process parameters affecting the layered composite and porosity.